Thermally Stable Forms of Pure Polyaniline Catalyzed by an Acid-Exchanged Montmorillonite Clay Called Maghnite-H+ as an Effective Catalyst - Rahmouni Abdelkader; Harrane Amine; Belbachir Mohammed (International Journal of Polymer Science)
Polyaniline salt form (PANI-ES) was synthesized by oxidative polymerization of aniline using potassium persulfate as an oxidant and an acid-exchanged montmorillonite clay called Maghnite-H+ as an effective catalyst. The clay, which was used as a catalyst, was supplied by a local company known as ENOF Maghnia (Western Algeria). The chemical stability of PANI has been investigated by thermogravimetry and differential scanning calorimetry, that a good thermal stability of PANI could be improved by combining PANI with montmorillonite. TGA results illustrated that there were two major stages for weight loss of the ES-form PANI powder sample. The different forms of PANI were characterized by infrared spectroscopy, thermal analysis, and H-NMR spectroscopy and conductivity measurements.